2020
DOI: 10.1088/1475-7516/2020/04/039
|View full text |Cite
|
Sign up to set email alerts
|

Parametrising non-linear dark energy perturbations

Abstract: In this paper we quantify the non-linear effects from k-essence dark energy through an effective parameter µ that encodes the additional contribution of a dark energy fluid or a modification of gravity to the Poisson equation. This is a first step toward quantifying non-linear effects of dark energy/modified gravity models in a more general approach. We compare our simulation results with predictions from the linear Boltzmann code CLASS. We show that for a large k-essence speed of sound the CLASS results are s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Thus, let us consider the perturbation condition by means of the adiabatic sound speed, c s , i.e., we assume the sound speed definition in adiabatic perturbations, in analogy to what happens in fluid dynamics [39,40]. So, defining the adiabatic sound speed by [41][42][43]:…”
Section: The Stability Condition and The Sound Speedmentioning
confidence: 99%
“…Thus, let us consider the perturbation condition by means of the adiabatic sound speed, c s , i.e., we assume the sound speed definition in adiabatic perturbations, in analogy to what happens in fluid dynamics [39,40]. So, defining the adiabatic sound speed by [41][42][43]:…”
Section: The Stability Condition and The Sound Speedmentioning
confidence: 99%
“…Here, the ratio P DE /P m is more suppressed in k-evolution than in CLASS, as the matter non-linearity is more effective than dark energy non-linearity, while inside the sound-horizon (on the very right of the left-hand panel, for redshifts, z = 0 and z = 1) we see the k-evolution result becoming larger than the one of CLASS, due to the effective clustering of dark energy at those scales. A more detailed study of the power ratio can be found in a companion paper [33].…”
Section: K-evolution Versus Classmentioning
confidence: 99%
“…Using the back-scaling approach it is not possible to obtain good results for both the matter density and the gravitational potential simultaneously. In a related paper [33] we present a possible approach to include a correction for the gravitational potential that addresses this problem.…”
Section: Newtonian Simulations With "Back-scaled" Initial Conditionsmentioning
confidence: 99%
“…• Modified gravity: Modified gravity N-body codes can be divided into two main categories: Newtonian codes with modified Poisson equation [2302][2303][2304], and relativistic codes [2305][2306][2307]. See Ref.…”
mentioning
confidence: 99%